Plantar Fasciitis: A Common and Underestimated Condition - A Review of the Current Literature - Kapturska, Natalia; Kardaszewski, Piotr; Cymerys, Kinga; Mąka , Magdalena; Kadłubek, Sabina; Woźniak, Julia; Kalinowski , Szymon; Kamiński, Jakub; Sikora, Dominik; Góralczyk, Ewa (Quality in Sport, 2026)
Introduction and purpose. Plantar fascia is a structure ensuring proper stabilization of the foot. Its malfunction impacts the organism as a whole. Untreated pathology leads to further health consequences. Plantar fasciitis (PF) is one of the most common and neglected foot pathologies. The knowledge on this topic is still insufficient. The purpose of this article is to consolidate current knowledge on plantar fasciitis. It is essential to highlight this problem, because it is a condition that continues to be underrepresented in scientific research. Material and methods. Medical databases including PubMed, Google Scholar and Embase were searched for scientific articles on risk factors, pathophysiology, symptoms, diagnostic methods, treatment and state of knowledge among society on plantar fasciitis. The identified studies were analyzed and combined into a single article. State of knowledge. One in ten people develops PF. Its peak incidence ranges from 40 to 60 years old. It occurs in athletic and non-athletic populations. There is no clear consensus among researchers on possible risk factors. Plantar Fasciitis leads to sharp pain at the plantarmedial aspect of the heel. The diagnosis is based on medical history and physical examination. There are numerous methods used in treatment of PF. Not all of them are scientifically proven but they are clinically successful when used. There is still a lack of research on prevention of PF. Awareness of the existence of this medical condition is not sufficient in the general population. Conclusions. Plantar fasciitis is a common yet underrepresented condition in scientific research, with many studies limited by small sample sizes and short follow-up periods. Increasing awareness of risk factors is essential, as untreated plantar fasciitis may become chronic. Although various treatment options exist, preventive measures remain insufficiently studied despite their importance.